Innovation of Aluminum Waste Fuel Stove - R Dwi Pudji Susilo; Mohamad Abror; Muhamad Fitri; M. Azizi; Dafit Feriyanto; Darwin Sebayang (Universitas Sultan Ageng Tirtayasa, 2024)
Aluminum waste is a challenging material to manage due to its high production rate from households and industries. This study aims to repurpose aluminum waste into hydrogen gas, which can serve as an alternative fuel for gas stoves. Direct disposal of aluminum waste can lead to environmental damage; hence, this project focuses on developing a system that dissolves aluminum using sodium hydroxide (NaOH) to produce hydrogen gas in a tube reactor. This hydrogen is then used as stove fuel. The comparison between aluminum-fueled hydrogen and conventional fuels, such as Pertalite and LPG, suggests that aluminum waste has potential as a cost-effective fuel source. For instance, one liter of Pertalite at Rp. 10,000 powers a motorbike for approximately 30 km, translating to Rp. 1,428 for a similar distance with aluminum-derived fuel. A 3 kg LPG cylinder costs around Rp. 24,000 and provides 10 hours of fuel, whereas hydrogen produced from aluminum can be cheaper if sourced from waste. Additionally, this design incorporates a refillable reactor that sustains hydrogen supply during combustion, ensuring consistent stove operation. The system is portable, safe, and offers high mobility, making it practical for various applications. This approach not only reduces aluminum waste but also presents an affordable alternative fuel solution, enhancing environmental sustainability.